NILAI EKONOMIS TERNAK SAPI PERAH SEBAGAI ALTERNATIF INVESTASI (STUDI KASUS di DESA TAJUK, KEC GETASAN, KAB SEMARANG) - -, wanuri; -, basukiyanto -; indriyaningrum, kis - (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2012)
This study aimed to assess the appropriateness of the dairy cattle business as an investment alternative, the role of the dairy cattle business in increasing farmers' income and the constraints that need to be solved in the beef cattle business. The study object is the dairy farmers in the district Getasan Semarang District. Required data obtained by questionnaires and interviews. For an analysis of the economic value of dairy cows performed by economic profitability, net pressent Value, Risk business benefits for the community. Economically business less profitable dairy cows. Farmer income from the business is relatively small. This condition is exacerbated by the high business risk cattle, characterized by sensitivity obtained keuntungaan farmers to changes in costs. The main cause is the small income market srtuktur cow's milk tend to be monopolistic. Keywords: Economic ValueÂ Â Â